Self Confidence and the Cognitive Styles among the Secondary School Students in Sri Lanka - Liyadipita L.A.M.H.P. (Kelaniya Journal of Management, 2021)
The purpose of this study was to determine secondary school students' self-confidence in terms of cognitive style. The dependent variable was self-confidence and independent factors were gender and cognitive styles. The study used a descriptive survey and the sample consisted of 400 students in grade 11. Data was collected using the Cognitive Style Inventory and the Self-confidence Inventory and was analyzed using a two-way ANOVA. Data were analyzed using Two Way ANOVA with a 52-factorial design. The most important influence of cognitive style and gender on secondary school pupils' self-confidence was shown to be substantial. The double interaction impact of cognitive style and gender on secondary school students' self-confidence was discovered to be substantial. School teachers should organize classes by employing active teaching strategies, suitable teaching tactics, and aiding students in developing academic self-confidence. Lectures, workshops, and seminars should be provided to students who are falling behind owing to poor cognitive style selection.